2022
DOI: 10.1177/00369330221117557
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Association between C-reactive protein levels and development of post-stroke depression: A systematic review and meta-analysis

Abstract: Background and aims Different prospective cohort studies have focused on the C-reactive protein ( ie, a pentameric protein) biomarker as a predictor of post-stroke depression. In this review and meta-analysis, we will attempt to synthesize the evidence for the association between C-reactive protein and the development of post-stroke depression. Methods We systematically searched five academic databases for relevant studies according to the PRISMA guidelines. We evaluate the comparative levels of C-reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Moreover, a meta-analysis demonstrated that elevated CRP is associated with the increased possibility of all-cause mortality in acute ischemic stroke subjects. Another study concluded that abnormal CRP may be linked to the stenosis of some cerebral arteries, and also, elevated hsCRP can possibly predict post-stroke disability, apathy, delirium, fatigue, cognitive impairment, and depression [550][551][552][553][554][555][556][557]. However, it was noted that the importance of CRP in ischemic stroke maybe less in older adults than in middle-aged populations, whereas the rapid post-stroke or post-MI hsCRP measurements showing an acute increase are not reflective of pre-stroke levels and may be less reliable for long-term risk stratification [77].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Moreover, a meta-analysis demonstrated that elevated CRP is associated with the increased possibility of all-cause mortality in acute ischemic stroke subjects. Another study concluded that abnormal CRP may be linked to the stenosis of some cerebral arteries, and also, elevated hsCRP can possibly predict post-stroke disability, apathy, delirium, fatigue, cognitive impairment, and depression [550][551][552][553][554][555][556][557]. However, it was noted that the importance of CRP in ischemic stroke maybe less in older adults than in middle-aged populations, whereas the rapid post-stroke or post-MI hsCRP measurements showing an acute increase are not reflective of pre-stroke levels and may be less reliable for long-term risk stratification [77].…”
Section: Neurological Disordersmentioning
confidence: 99%